The choice of resources and the investigation process: Case studies in France and Morocco - Lougman, A.; Mourabit, M. El; Merabet, Y. El (Edelweiss Applied Science and Technology, 2024)
Learning science through ‘rediscovery’ is an old story that was thought up by Charles Brunold (Astolfi Jean-Pierre, 2014). This approach aimed to get pupils who wanted to be active to rediscover scientific results, but « it has to be said that even today, we hardly go beyond this issue when we talk about getting pupils to participate » (ibidem, 2014). This is because such teaching (the teaching of results) can only be described as scientific if the reasons that led to these results are made explicit (Bachelard, 1938, p. 234). In this context, Jaubert and Ribière specify that the construction of knowledge is inseparable from the appropriation of practices, including language practices.